Problem Channel Dakwah Melalui Media Sosial dalam Memupuk Toleransi Beragama di Indonesia - Azharghany, Rojabi; Lusi Kurnia Agustin; Echa Edelweiss Putri Andina (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2024)
The development of Islamic da'wah channels through social media not only has a positive impact on the spread of understanding of Islamic religious practices, but also poses problems in fostering religious tolerance in Indonesia. So far, the study of the development of social media da'wah channels has only seen the positive side of the use of social media in its ease and speed of reaching all circles for the dissemination of understanding of various Islamic practices. This research wants to complement the trend of previous studies that only see the positive side of the development of Islamic da'wah channels in the ease and speed of spreading the understanding of Islamic religious practices in Indonesia. The unit of analysis in this study is the Islamic da'wah channel on YouTube, using a qualitative design and data collection is carried out through desk-review. Data analysis is carried out through data reduction, data display, data verification, and content analysis and interpretation. The results of the study showed three main problems: limited confirmation space, counter-tolerance, and horizontal conflict. Limited confirmation space leads to the dissemination of inaccurate information, counter-tolerance worsens interfaith relations, and horizontal conflicts trigger debate and tension. This research provides recommendations to increase content moderation and education about the importance of religious tolerance on social media.